Accounting of pay-as-you-go pension schemes using accrued-to-date liabilities: An example for Switzerland - Christoph Metzger (Albert-Ludwigs-Universität Freiburg, Forschungszentrum Generationenverträge (FZG), 2016)
Due to demographic change, the fiscal sustainability of pension schemes financed on a pay-as-you-go (PAYGO) basis is of more interest for policy makers than ever. Unsustainable financing brings along a future burden to pensioners through pension cuts and/or to the working population through increasing contribution rates. With comparable data about the unfunded accrued-to-date pension liabilities of social security pension schemes soon being available due to a recent update of the international System of National Accounts (2008 SNA), we present a simple framework for accounting of paygo pension schemes using these estimates of accrued-to-date liabilities. Additionally we incorporate another definition of liabilities, the current workers' and pensioners' net liabilities (CWL). Applying this accounting framework using both definitions of liabilities to the Swiss pension scheme (AHV), we show that financing of the AHV is unsustainable. In order to restore fiscal sustainability either an increase in the contribution rate to 12 percent or a cut in average pension levels of about 38 percent would be necessary.
Keywords: E01; H55; H83; H87; 330; accounting of pension schemes; accrued-to-date liabilities; supplementary table; fiscal sustainability